Daya Terima Coffee Jam dengan Subtitusi Jahe (Zingiber officinale) - Zainuddin, Nurul Muchlisah; Achmad, Fadhilah; Aisyah, Dwi Citra Nurul (Program Studi Teknologi Pangan, 2025)
Coffee jam is a form of product diversification using coffee as its base ingredient. This research contains about making coffee jam with the addition of ginger extract. The addition of ginger as an additional ingredient for making coffee jam is a form of product fortification. The process of making coffee jam starts from preparing tools and materials, weighing, mixing additional ginger ingredients, cooking, cooling and packaging. This research was carried out at the Agricultural Technology Laboratory, Faculty of Agriculture, Cokroaminoto University, Makassar in March-April 2024. The treatments in this research were the addition of ginger and without the addition of ginger, 0 g, 25 g, 45 g, and 75 g. This research was conducted using a descriptive method by analyzing the public's response to the aroma, taste, spreadability and color of coffee jam. Based on the analysis of organoleptic tests or people's acceptance of coffee jam, in this case the aroma, taste, spreadability and color that the panelists liked most was the addition of 45 g of ginger. The treatment with 45 grams of ginger produced the aroma, taste, spreadability and color values that were most liked by the panelists.